Population dynamics of climbing perch fish (Anabas testudineus) in the waters of Tempe Lake, Wajo Regency, South Sulawesi - Siti Khadijah Srioktoviana; Faisal Amir; Achmar Mallawa (Jurnal IPTEKS Pemanfaatan Sumberdaya Perikanan, 2022)
Climbing perch (Anabas testudienus) is one of the inhabitants of Lake Tempe exploited throughout the year, so it is feared that its population has decreased. This study aims to analyze aspects of the dynamics of the climbing perch population, including age group, population growth, mortality, exploitation rate, and yield per recruitment. Data on the total length of fish were collected by measuring all catches of fishermen from October to December 2021. Age groups were analyzed using the Battacharya method, L∞ and K used the Ford and Walford method, M used the Empiris Pauly method, Z, F, and E used the Beverton and Holt method. Data analysis using FISAT-II software and Microsoft Excel. The results showed that the climbing perch in the waters of the Lake Tempe Wajo Regency had a total length range of 6 – 20.8 cm, the highest catch was in the middle-class size of 11.5 – 13.5 cm, and the average length is 13.03±2.15 cm. The population consists of two age groups, the estimated value L∞ = 26.3 cm, K = 0.5 year-1 and t0 = -0.3384 years. The estimated Z, M and F values are 3.41 year-1, 1.22 year-1, and 2.19 year-1, respectively. The exploitation rate is 0.64 year-1, and the actual and optimal Y/R are 0.015gram recruitment-1 and 0.0163 gram recruitment-1, respectively. The conclusion is that climbing perch in the waters of Lake Tempe  Wajo Regency require a short time to reach the maximum length, the main cause of population death due to fishing, and the recruitment process is not optimal due to the high rate of exploitation.